The Factors Behind Spelling Errors Among Students At Islamic-Based School Surabaya - Rahmawati, Sustania; Imaniar, Fahmy (Jurnal Ilmiah Wahana Pendidikan, 2024)
The article discusses the challenges faced by 7th grade students at an Islamic-based school in Surabaya in learning english spelling. The purpose of the article is to identify the factors behind students' English language learning and to propose effective strategies for improving their motivation and language skills. The article conducted qualitative method through observations to the students and interview one of the English teacher at an Islamic-based school in Surabaya. The article identifies several factors behind students' English language learning, including a lack of motivation, too much vocabulary to be mastered, differences in writing and pronunciation, and a lack of practice. The article concludes that the lack of interest in learning English is the primary factor behind students' language learning, as it can influence other factors. The article emphasizes the importance of consistent practice and the need for teachers to provide innovative and enjoyable strategies to increase students' motivation for learning English.